Educação profissional no Brasil e a interiorização do Instituto Federal de São Paulo : trajetórias e lógicas da expansão - Estevo, Marcio Rogério Tomazzi (2016)
Brazilian schools known as “Institutos Federais” (Federal Institutes), and the expansion of their campuses are presented here as a possibility to tackle national challenges and to outperform old professional educations paradigms. So in this work we try to check the possible relations that exist between the technological axis implemented on the new campuses and the local productive arrangements. This work is based on case analysis with bibliographic and documental research, analysis of socioeconomic data, semi-structured interviews with representative actors, visits to the campuses and reflections using the structural and historical analysis method. In section 1 the theme is introducted and presented. In section 2 we make a conceptual exposition about Professional Education, and the relation between education, work, development, knowledge, Local Arrangements, their disputes and tendencies. We also discuss the diverse objectives of Professional Education, sometimes aiming the individual, sometimes aiming the centrality of the market, this duality being persistent even after some tentative reformations. We also discuss the formal education as a means to emancipate people, cause social transformation, or to conciliate development, inequalities reduction and democracy. In section 3 we present the history of the Professional Education, highlight the main facts that lead to the resuming of the Professional and Technological Education Federal Network (“Rede Federal de Educação Profissional e Tecnológica - RFEPT”) and to the creation of the Federal Institutes, during Lula's government. We highlight the centenary of this network, and the conflicting projects for educations and national development. In section 4, we explore the peculiarities of the Federal Institute of São Paulo (“Instituto Federal de São Paulo - IFSP”), a new, but also old, institution, focusing on its campus at the city of Araraquara, and the contextualization of the development of this region of São Paulo State, leading actor of the national development. The city of Araraquara is an important city of the central region of the State, and also Seat of a Government Region. To achieve this objective, we use the research made by Maria Teresa Miceli Kerbauy. We explore, mainly by interviews with representative people, the campus installed at Araraquara, and its role in the region, this campus participates on the phase II of the expansion plan of the Network. The contextualization uses socioeconomic data from Fundação Seade and the approach of political leadership. On the last section, we make remarks and reflections about IFSP, its mission, its identity, its priorities and the possible priority of its relation with the region, as stated by Law 11.892 of December, 29, 2008, that was the law that created the Federal Institutes. We also look for pointing directions for new actions and new studies. We conclude that this expansion is beyond its transformations potential and confirm the hipothesis of the influence of other factors beyond the locality, on the definition of new courses to be implementes on the new campuses.